Attorney-client privilege in international arbitration - Möckesch, Annabelle (Oxford international arbitration series., 2017)
Attorney-client privilege is often invoked as a defence in international arbitration proceedings however the participants often have very different expectations regarding the applicable privilege standard, as national attorney-client privilege laws vary widely between jurisdictions. This is complicated by the fact that institutional arbitral rules do not include provisions on the scope of attorney-client privilege, nor do they outline the conflict of laws issues determining the applicable national privilege law. The applicable level of privilege is therefore left to the discretion of the arbitral tribunal. Drawing on interviews with more than thirty leading international arbitration practitioners and extensive academic research, this book is the first of its kind to provide clear guidance to arbitral tribunals regarding the determination of the applicable attorney-client privilege standard. It compares attorney-client privilege in key common and civil law jurisdictions, analyses precedent from previous tribunals, and finally sets out proposed changes to the legal framework governing this area.--